The role of mucosal-associated invariant T cells in visceral leishmaniasis - Moreira, Marcela de Lima; Borges-Fernandes, Luana Oliveira; Pascoal-Xavier, Marcelo Antônio; Ribeiro, Ágata Lopes; Pereira, Victória Hellena Silva; Pediongco, Troi; Araújo, Márcio Sobreira da Silva; Teixeira-Carvalho, Andréa; de Carvalho, Andrea Lucchesi; Mourão, Maria Vitória Assumpção; Campos, Flávia Alves; Borges, Marineide; et al. (Frontiers in Immunology, 2022)
Mucosal-associated invariant T (MAIT) cells are restricted by MR1 and are known to protect against bacterial and viral infections. Our understanding of the role of MAIT cells in parasitic infections, such as visceral leishmaniasis (VL) caused by protozoan parasites of Leishmania donovani, is limited. This study showed that in response to L. infantum, human peripheral blood MAIT cells from children with leishmaniasis produced TNF and IFN-γ in an MR1-dependent manner. The overall frequency of MAIT cells was inversely correlated with alanine aminotransferase levels, a specific marker of liver damage strongly associated with severe hepatic involvement in VL. In addition, there was a positive correlation between total protein levels and the frequency of IL-17A+ CD8+ MAIT cells, whereby reduced total protein levels are a marker of liver and kidney damage. Furthermore, the frequencies of IFN-γ+ and IL-10+ MAIT cells were inversely correlated with Haemoglobin levels, a marker of severe anaemia. In asymptomatic individuals and VL patients after treatment, MAIT cells also produced IL-17A, a cytokine signature associated with resistance to visceral leishmaniasis, suggesting that MAIT cells play important role in protecting against VL. In summary, these results broaden our understanding of MAIT-cell immunity to include protection against parasitic infections, with implications for MAIT-cell-based therapeutics and vaccines. At last, this study paves the way for the investigation of putative MAIT cell antigens that could exist in the context of Leishmania infection.